Markets and Value Chain Study of Major Commodities in the Dryland Regions of Maharashtra: Technical report - Pramanik, Soumitra; Das, Abhishek; Patan, Elias Khan; Majeed, Israr Reshi; Anantha, Kanugod H.; Garg, Kaushal K.; Singh, Ramesh; Kumar, Shalander (International Crops Research Institute for the Semi-Arid Tropics, 2025)
The International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), in partnership with the Ground Water Surveys and Development Agency (GSDA), is conducting a collaborative study focused on improving agricultural systems and livelihoods in rural Maharashtra, India. The study emphasizes both resource efficiency and enhanced agricultural productivity. It also explores sustainable farming practices and effective market integration for smallholder farmers. The central goal is to support rural communities by strengthening natural resource management, introducing climate-resilient farming techniques, and improving market access for key agricultural commodities. This initiative adopts a comprehensive approach to agricultural development, combining economic advancement with ecological sustainability and social empowerment. By equipping farmers with improved knowledge and practices and strengthening linkages across the agricultural value chain—from production to market—the project seeks to improve farmers’ incomes and reduce their vulnerability to climate and market risks. A critical focus of the study is on optimizing the use of land and water resources while promoting farming systems that are both environmentally responsible and economically viable. The project also seeks to identify and promote region-specific innovations that align with agro-ecological conditions and local market opportunities. Improved market access is a core pillar of this intervention. By enhancing the efficiency of input supply chains and improving the terms under which farmers engage with output markets, the project aims to ensure that smallholder producers receive fair returns for their produce. Stronger value chain integration will also increase the availability of quality inputs and improve the competitiveness of rural farmers in regional markets.